Effect of fibre arrangement on the multiaxial fatigue of fibrous composites: a micromechanical computational model (Fracture and Structural Integrity, 2015)
Structural components made of fibre-reinforced materials are frequently used in engineering applications. Fibre-reinforced composites are multiphase materials, and complex mechanical phenomena take place at limit conditions but also during normal service situations, especially under fatigue loading, causing a progressive deterioration and damage. Under repeated loading, the degradation mainly occurs in the matrix material and at the fibre-matrix interface, and such a degradation has to be quantified for design structural assessment purposes. To this end, damage mechanics and fracture mechanics theories can be suitably applied to examine such a problem. Damage concepts can be applied to the matrix mechanical characteristics and, by adopting a 3-D mixed mode fracture description of the fibre-matrix detachment, fatigue fracture mechanics concepts can be used to determine the progressive fibre debonding responsible for the loss of load bearing capacity of the reinforcing phase.In the present paper, a micromechanical model is used to evaluate the unixial or multiaxial fatigue behaviour ofstructures with equi-oriented or randomly distributed fibres. The spatial fibre arrangement is taken into account through a statistical description of their orientation angles for which a Gaussian-like distribution is assumed, whereas the mechanical effect of the fibres on the composite is accounted for by a homogenization approach aimed at obtaining the macroscopic elastic constants of the material. The composite material behaves as an isotropic one for randomly distributed fibres, while it is transversally isotropic for unidirectional fibres. The fibre arrangement in the structural component influences the fatigue life with respect to the biaxiality ratio for multiaxial constant amplitude fatigue loading. One representative parametric example is discussed.
Keywords: Fibres